THE CONTENT AND METHODOLOGICAL FOUNDATIONS OF THE DEVELOPMENT OF TECHNICAL CREATIVITY OF STUDENTS (Scientific journal of the Fergana State University, 2026)
This article provides a comprehensive analysis of the development of students' technical creativity from a scientific and pedagogical perspective. The author presents technical creativity not only as an integral part of professional activity but also as a central goal of modern technological education. The relevance of the topic lies in the growing need to train specialists with creative and independent thinking, capable of competing in today’s labor market. The article systematically highlights methodological approaches, instructional tools, and psychological components essential for nurturing professionally creative individuals within the technological education framework. The author’s proposals and conclusions are practically oriented and emphasize the need to integrate related subjects, apply differentiated approaches, and ensure deep knowledge of technical fundamentals. This article is a valuable resource for researchers, educators, and professionals working on educational reforms in the field of technical creativity development.